2017
DOI: 10.1149/2.0231708jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cycle Performance of Quinone-Based Anodes for Sodium Ion Batteries by Attachment to Ordered Mesoporous Carbon and Use of Ionic Liquid Electrolyte

Abstract: Sodium ion batteries (SIBs) have emerged as a potential alternative to lithium ion batteries due to their chemical similarities. Key considerations for SIBs include energy storage capacity, lifetime, cost, and safety. Major challenges associated with high performance organic electrodes for rechargeable batteries are their poor electrical conductivity and dissolution of the active material in common electrolytes. The poor conductivity limits the rate performance, while dissolution leads to poor cycle performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…[ 101 ] The same electrolyte composition was employed in sodium cells in combination with a Sb 2 S 3 /graphene anode material, showing superior performance compared to conventional carbonate‐based electrolyte. [ 102 ] Owing to its superior properties, Pyr 13 FSI–NaFSI has been applied for SIBs by several other research groups in different cell configurations, [ 103–107 ] nevertheless it is interesting to note the effects that the salt anion has on the performance and accordingly there is certainly much room to improve these IL‐based electrolytes for future applications. Furthermore, while there has been significant investigation of the behavior of the electrode/electrolyte interphase in organic electrolytes, as discussed above, there is a lesser understanding of the interphase in the IL‐based systems.…”
Section: Electrolytes For Na‐based Rechargeable Batteriesmentioning
confidence: 99%
“…[ 101 ] The same electrolyte composition was employed in sodium cells in combination with a Sb 2 S 3 /graphene anode material, showing superior performance compared to conventional carbonate‐based electrolyte. [ 102 ] Owing to its superior properties, Pyr 13 FSI–NaFSI has been applied for SIBs by several other research groups in different cell configurations, [ 103–107 ] nevertheless it is interesting to note the effects that the salt anion has on the performance and accordingly there is certainly much room to improve these IL‐based electrolytes for future applications. Furthermore, while there has been significant investigation of the behavior of the electrode/electrolyte interphase in organic electrolytes, as discussed above, there is a lesser understanding of the interphase in the IL‐based systems.…”
Section: Electrolytes For Na‐based Rechargeable Batteriesmentioning
confidence: 99%
“…36,37 Besides, IL-based electrolyte possesses advantages over organic electrolyte, such as low flammability, negligible volatility, and higher thermal and electrochemical stabilities. [38][39][40][41] Inspired by these merits, an interesting question arises as to whether ILs have inhibitory effect toward the dissolution of quinone electrode materials. However, as far as we know, there is scarcely any report on the combined use of ILs and quinone cathode for SIBs, let alone mechanism investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies using ILs have reported enhanced electrochemical performances over wide temperature ranges, and in particular at intermediate temperatures . In particular, negative electrodes with high volume changes showed clear improvements in performance when ILs were employed due to the formation of a robust and stable SEI layer . For example, a combination of red phosphorus with 0.25 M Na[FSA]‐[C 3 C 1 pyrr][FSA] (FSA: bis(fluorosulfonyl)amide anion and C 3 C 1 pyrr + : N ‐propyl‐ N ‐methylpyrrolidinium cation) showed a good cyclability attributed to the uniform and stable SEI layer, as revealed by hard X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%